Embracing Change: Conversations about Adult Education and Activism through Autoethnography - Roy, Carole; Hanson, Cindy (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2024)
Carole and Cindy first met at a conference on transformative learning, By the People, at Arizona State University in December 2015. That meeting and many others that followed (usually in conjunction with Canadian Association for the Study of Adult Education) have brought about vibrant conversations about activism, adult learning, and community work. These conversations have served as a catalyst for the telling and analysis of our varied life stories. Through this special issue we share some of our journeys and those of other adult educators from North America.